Instrumentation of the combined processes in water treatment technology - V. V. Borodychev; A. E. Novikov; M. I. Lamskova; M. I. Filimonov (Новые технологии, 2020)
An increase in the volume of industrial effluents, ship accidents, oil breakthroughs at drilling rigs lead to a deterioration in the quality indicators of water in open water sources, including in terms of the content of organic compounds and oil products. The water used for irrigation of agricultural crops, according to most indicators, must meet the water quality requirements for household and drinking purposes. Thus, the total content of oil products in the irrigation water should not exceed 0.1 mg / l. The use of water with the MPC excess leads to significant changes in the morphological properties of the soil, reduces the biological productivity and phytomass of the plant cover. Therefore, the issue of improving machines and devices used in water treatment technologies to increase their reliability and efficiency is one of the topical areas of the research. The aim of the study is to develop a hydrocyclone complex cleaning apparatus, which implements combined processes of capturing both coarse and finely dispersed impurities. Unlike the standard design, the hydrocyclone is supplemented with a filter element installed on the drain pipe, which provides additional water purification from fine mechanical impurities, and a sorption filter designed to remove oil products and other floating organic compounds from water. The proposed hydrocyclone unit provides a comprehensive purification of irrigation water from various types of impurities, due to the combined processes of centrifugal separation and sorption filtration. It eliminates the multistage process of water purification, and regeneration of the sorption filter by the action of centrifugal forces or pressure does not require the use of special regenerating solutions, which increases the manufacturability and environmental friendliness of the water treatment process.